SERVERLESS ARCHITECTURES: A COMPARATIVE STUDY ON ENVIRONMENTAL IMPACT AND SUSTAINABILITY IN GREEN COMPUTING - Shantanu Kumar, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
Cloud computing has grown very quickly, which has made serverless architectures possible. These architectures offer unmatched scalability, cost-effectiveness, and lower operating overhead. However, the effects of this paradigm shift on the environment are still mostly unknown, especially when it comes to global sustainability and green computing efforts. The purpose of this study is to fill in this gap by looking at how energy-efficient and environmentally friendly serverless computing is compared to traditional cloud and on-premises options. This research looks at the carbon footprint of serverless architectures, the green policies of big cloud providers, and ways to make serverless apps work better so they have less of an effect on the environment. This study takes a broad look at serverless computing to find out what role it plays in lowering the IT industry's carbon footprint. The goal is to give developers, cloud providers, and lawmakers useful information that they can use to promote green computing.